Informative pedagogic control indicators of 14-15 years age girls' motor fitness - O.V. Ivashchenko; O.O. Kapkan (H.S. Skovoroda Kharkov National Pedagogical University, 2016)
Purpose: to determine informative indicators for in-group and intra-group control of 14-15 years age girls' motor fitness. Material: in the research 99 girls participted: 14 years old (n=38), 15 years old (n=61). Results: for control of 15 years age girls' motor fitness the most informative are indicators of speed power, dynamic power endurance and physical condition. It was found that 14 years age girls have better power fitness than 15 years girls. It points at the fact that in 15 years' age the reasons of lagging behind 14 years girls are increase of body mass and reduction of motor activity. Conclusions: the received data show that factorial analysis as well as discriminant one is methodological base for determination of tests' in-group and intra-group informational potential. The most informative tests for determination of age dynamic are static and dynamic power endurance of abdomen muscles and connected with them result of long jumps from the spot.